Dietary intervention in depression – a review. Issue 24 (21st November 2022) - Wu, Tao; Liu, Ran; Zhang, Ling; Rifky, Mohamed; Sui, Wenjie; Zhu, Qiaomei; Zhang, Jiaojiao; Yin, Jinjin; Zhang, Min
Abstract : Probiotics, micronutrients and other active substances by regulating the pathways such as tryptophan metabolism and inflammation showed significant antidepressant effects. These provide insights for developing antidepressant foods. Abstract : Depression is a mental illness that affects the normal lives of over 300 million people. Unfortunately, about 30% to 40% of patients do not adequately respond to pharmacotherapy and other therapies. This review focuses on exploring the relationship between dietary nutrition and depression, aiming to find safer and efficient ingredients to alleviate depression. Diet can affect depression in numerous ways. These pathways include the regulation of tryptophan metabolism, inflammation, hypothalamic–pituitary–adrenal (HPA) axis, microbe–gut–brain axis, brain-derived neurotrophic factor (BDNF) and epigenetics. Furthermore, probiotics, micronutrients, and other active substances exhibit significant antidepressant effects by regulating the above pathways. These provide insights for developing antidepressant foods.